Pengaruh Sales Promotion dan Hedonic Browsing Terhadap Online Impulsive Buying Behavior Pelanggan E-Commerce: Studi Kasus di Kota Surabaya - Dea Rachma Sucita; Nadila Kusuma Wardani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
E-commerce is the use of electronic media platforms to sell products or services. It can be end-to-end, where customers can complete the entire purchasing process from product discovery, negotiation, to transaction without leaving the application. The purpose of this study was to determine whether sales promotions and hedonic browsing influence online impulsive buying behavior. The research method used was quantitative. Based on the sample determination conducted using the non-probability sampling method (purpose sampling technique), this study used 149 respondents in the city of Surabaya. The sample was determined based on the minimum sample formula, where the number of indicators is multiplied by a factor between 5 and 10, resulting in a minimum sample of 120. Data analysis used Partial Leave Square (PLS). The results showed that sales promotions did not have a significant effect on online impulsive buying behavior in Surabaya. This suggests that sales promotion efforts, such as discounts or special offers, may not have a significant impact on customers' online impulsive buying decisions. Hedonic browsing has a significant effect on online impulsive buying behavior in Surabaya. So this can provide valuable insights for e-commerce players to focus more on marketing efforts and hedonic shopping experiences to increase online impulse purchases from customers in Surabaya City.